Prediction of biomarker peak of infrared spectra between pork fat and chicken meat fat using fourier transform infrared spectroscopy technique and clotter plot method - Saputra, Irwan; Kartika, Irma Ratna (Journal of Halal Science and Research, 2024)
The increasingly widespread contamination of chicken meat by pork requires a method to identify the presence of these contaminants quickly and cheaply. Apart from analyzing the spectrum of various pure animal fats, this research also aims to vary the concentration of pork fat and chicken fat to know the FTIR peak spectrum, which will change with changes in concentration. The presence of spectral peaks that change can be identified due to changes in pork fat concentration, which also shows a typical peak spectrum position in pork fat. Variations in the concentration of pork fat contaminants in chicken fat consist of the ratio of the mixture of pork fat (PF) and chicken fat (CF), namely 90:10 (PC1), 80:20 (PC2), 70:30 (PC3), 60:40 (PC4), 50:50 (PC5), 40:60 (PC6), 30:70 (PC7), 20:80 (PC8), and 10:90 (PC9). A scatter plot, a graph usually used to see the relationship pattern between 2 variables, is employed in this research to visualize the changes in spectral peaks with varying concentrations of pork fat in chicken fat. The data scale must be an interval and ratio scale to use a scatter plot. Biomarker wavelengths were identified from the spectra of four animal fats and palm oil at positions 2948.9 and 3007 cm−1, separated by four animal fats and palm oil at a certain distance, thus indicating that these wavelengths could be used to identify non-halal samples.   Keywords: Chicken, Clotter plot, Fat, Infrared, Meat, Pork, Spectra